2002
DOI: 10.1038/sj.bjc.6600182
|View full text |Cite
|
Sign up to set email alerts
|

ZD1839 (‘Iressa’), a specific oral epidermal growth factor receptor-tyrosine kinase inhibitor, potentiates radiotherapy in a human colorectal cancer xenograft model

Abstract: The effect of ZD1839 (‘Iressa’), a specific inhibitor of the tyrosine kinase activity of the epidermal growth factor receptor, on the radiation response of human tumour cells (LoVo colorectal carcinoma) was evaluated in vitro and in vivo . ZD1839 (0.5 μ M , incubated days 1–5) significantly increased the anti-proliferative effect of fractionated radiation treatment (2 Gy day −1 , days 1–3) on LoVo cells grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(50 citation statements)
references
References 16 publications
1
48
1
Order By: Relevance
“…Similar enhancement of activity has also been observed in studies combining EGFR-targeting agents, particularly the monoclonal antibody IMC C225 (cetuximab), with ionizing radiation (Huang et al, 1999;Saleh et al, 1999;Bianco et al, 2000;Bonner et al, 2000;Milas et al, 2000). Other investigators (Williams et al, 2002) and this laboratory (Magné et al, 2002a) recently showed supra-additive effects between irradiation and ZD1839, confirming the radiosensitisation conferred by an EGFRtargeting agent. We also reported a synergistic interaction between ZD1839 and the cisplatin -5FU combination (Magné et al, 2002a).…”
mentioning
confidence: 58%
“…Similar enhancement of activity has also been observed in studies combining EGFR-targeting agents, particularly the monoclonal antibody IMC C225 (cetuximab), with ionizing radiation (Huang et al, 1999;Saleh et al, 1999;Bianco et al, 2000;Bonner et al, 2000;Milas et al, 2000). Other investigators (Williams et al, 2002) and this laboratory (Magné et al, 2002a) recently showed supra-additive effects between irradiation and ZD1839, confirming the radiosensitisation conferred by an EGFRtargeting agent. We also reported a synergistic interaction between ZD1839 and the cisplatin -5FU combination (Magné et al, 2002a).…”
mentioning
confidence: 58%
“…6 Also, gefitinib has shown antitumoral activity against a range of human tumor xenografts. 7 To see if any other types of human cancers besides NSCLC carry the EGFR mutations, we analyzed 537 tissue samples from common human cancers, including 98 colon adenocarcinomas, 185 gastric adenocarcinomas, 93 breast ductal carcinomas, 73 hepatocellular carcinomas and 88 acute adulthood leukemias by polymerase chain reaction (PCR)-single strand conformation polymorphism (SSCP) analysis. Malignant cells and normal cells were selectively procured from hematoxylin and eosin-stained slides using a 30G1/2 hypodermic needle (Becton Dickinson, Franklin Lakes, NJ) affixed to a micromanipulator, as described previously.…”
Section: Dear Sirmentioning
confidence: 99%
“…Because gefitinib had an anti-cancer activity in wide types of cancer cell lines and the EGFR kinase domain mutation is known to mediate the gefitinib sensitivity, 6,7 we expected that human cancer tissues would widely carry EGFR mutations. However, our data showed that EGFR kinase domain is very rarely mutated in common human cancers besides NSCLC.…”
Section: Dear Sirmentioning
confidence: 99%
“…Recent studies have suggested that gefitinib induces cell cycle retardation and apoptosis, and inhibits the growth of several types of human cancer cells expressing EGFR both in vitro and in vivo (Ciardiello et al, 2000;Sirotnak et al, 2000;Ciardiello et al, 2001;Moasser et al, 2001;Moulder et al, 2001;Bianco et al, 2002;Ciardiello et al, 2002;Fujimura et al, 2002;Huang et al, 2002;Janne et al, 2002;Magne et al, 2002;Williams et al, 2002). In addition, human breast cancer cells overexpressing HER2 or acquiring resistance to the oestrogen receptor (ER) antagonist, fulvestrant (Faslodex,ICI 182,780), have been reported to be particularly sensitive to gefitinib (McClelland et al, 2001;Moulder et al, 2001).…”
mentioning
confidence: 99%